(untitled) (Pakistan Journal of Kidney Diseases, 2021)
Abstract Hepatitis B virus (HBV) is a highly prevalent infection worldwide. It primarily infects liver and presents with features of chronic liver disease. Rarely, it presents with extra-hepatic manifestations. Kidney involvement in HBV infection is not uncommon. However, presentation with rapidly progressive glomerulonephritis is distinctly rare. A 40-year-old man with undiscovered HBV infection presented with fever-triggered body swelling for one month. Serum creatinine was 2.3 mg/dl on admission, which increased during hospitalization to 4.5 mg/dl. Renal biopsy demonstrated crescentic membranoproliferative glomerulonephritis, immune complex-mediated. Clinical, laboratory and imaging studies revealed mild chronic liver damage. Complete renal, hepatic and virological remission was achieved with steroids, plasmapheresis and antiviral therapy. This case emphasizes on early diagnosis and institution of multimodal therapy for better outcomes.